Barraza Jara, Eduardo. 2013. Adelantados y escritura de la conquista. Imaginarios historiográficos en la literatura chilena. Santiago de Chile: Editorial Universidad de Santiago de Chile. 289 pp. - Rodríguez, Osvaldo (2014)
Fil: Rodríguez, Osvaldo.